2018
DOI: 10.1002/hbm.24078
|View full text |Cite
|
Sign up to set email alerts
|

BrainMap VBM: An environment for structural meta‐analysis

Abstract: The BrainMap database is a community resource that curates peer-reviewed, coordinate-based human neuroimaging literature. By pairing the results of neuroimaging studies with their relevant meta-data, BrainMap facilitates coordinate-based meta-analysis (CBMA) of the neuroimaging literature en masse or at the level of experimental paradigm, clinical disease, or anatomic location. Initially dedicated to the functional, task-activation literature, BrainMap is now expanding to include voxel-based morphometry (VBM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 88 publications
1
69
0
Order By: Relevance
“…BrainMap is a neuroimaging database which, at the time of this study, (Kotkowski, Price, Fox, Vanasse, & Fox, 2018;Vanasse et al, 2018). We can use this function to independently quantify the degree of structural similarity between neurodegenerative diseases like AD and MetS using a z-score.…”
Section: Behavior Paradigm Class and Disease Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…BrainMap is a neuroimaging database which, at the time of this study, (Kotkowski, Price, Fox, Vanasse, & Fox, 2018;Vanasse et al, 2018). We can use this function to independently quantify the degree of structural similarity between neurodegenerative diseases like AD and MetS using a z-score.…”
Section: Behavior Paradigm Class and Disease Analysesmentioning
confidence: 99%
“…Two additional post hoc analyses involving the subdivided large group of 208 participants were performed using identical thresholds and permutations. In this analysis we divided participants by the median age (35.5 years) and grouped them into half samples termed "young" and Vanasse et al, 2018). We can use this function to independently quantify the degree of structural similarity between neurodegenerative diseases like AD and MetS using a z-score.…”
Section: Post Hoc Analysis On Age Effectsmentioning
confidence: 99%
“…The low split-sample similarity of single-subject maps emphasized the need to apply such classic neuroscience practices when analyzing these explanation maps. Next, we demonstrated that despite the methodological differences, the proposed map shows significant similarity with ALE maps from age VBM meta-analysis study (Vanasse et al, 2018), attesting to its convergence validity. Finally, using regional volumetric measures we demonstrated that brain regions highlighted by our method were found as the ones with the highest influence on the model's prediction, indicating the specificity of the derived maps to the current model.…”
Section: Identifying the Brain Regions Underlying Age Prediction Usinmentioning
confidence: 61%
“…In the current study, we used a published activation likelihood estimation (ALE) meta-analysis of age VBM studies (Vanasse et al, 2018). Here, by utilizing peak reported coordinates from several VBM studies (n = 43), the ALE analysis assigns each voxel the probability that it lies within a reported peak (Laird, Bzdok, Kurth, Fox, & Eickhoff, 2011).…”
Section: Benchmarking the Results Against A Standard Voxel-based Morpmentioning
confidence: 99%
See 1 more Smart Citation